Children Reception Centers: Main Challenges of the Present Day - N. V. Kolomoiets (Law and Safety)
The author of the article has studied the legal grounds for the functioning of children reception centers. While presenting the material the author has reflected the current conditions of minors stay in these institutions of the National Police of Ukraine and has revealed the competence of authorized persons, who work directly with children who enter the reception centers.